Experimental investigations on a standing - wave thermoacoustic engine - Mahmoud Mohamed Emam; Abdelmaged Hafez Ibrahim Essawy; Ehab Abdelrahman; Mahmoud Ahmed Fouad (Cairo : Mahmoud Mohamed Emam, 2013)
In the work both the transient and steady-state performance of the thermoacoustic engine are investigated using variable gas mixtures and using square-cell stacks of variable porosities . Transient engine performance is studied during full runs consisting of start - up steady operation and shutting down
Thesis (M.Sc.) - Cairo University - Faculty of Engineering - Department of Mechanical Power Engineering
Issued also as CD
Keywords: Engine; Hysteresis; Thermoacoustic